Future of work, work-family satisfaction, and employee well-being in the fourth industrial revolution - Abe, Ethel Ndidiamaka, 1966- (Advances in human resources management and organizational development (AHRMOD) book series., 2021)
""This book examines the future of work, work-family satisfaction, and employee well-being in the fourth industrial revolution"--Provided by publisher"--